Comparative evaluation of treatment patterns and healthcare utilization of newly-diagnosed rheumatoid arthritis patients by anti-cyclic citrullinated peptide antibody status. (4th March 2018) - Lamerato, Lois; Price, Kwanza; Szymialis, Rick; Eaddy, Michael; Ogbonnaya, Augustina; Shih, Huai-Che; Ahmad, Harris
Abstract: Background: Anti-cyclic citrullinated peptide (CCP) antibody positivity is an established diagnostic factor for severe disease activity and joint damage and a prognostic factor for aggressive disease in rheumatoid arthritis (RA). Objective: To compare RA-related treatment, healthcare utilization, and joint erosion between anti-CCP-positive and anti-CCP-negative RA patients. Methods: Newly-diagnosed RA patients were identified from the Henry Ford Health System database between January 1, 2009 and December 31, 2014; the date of the first RA diagnosis within the study period was the index date. Baseline anti-CCP test was used to categorize patients as anti-CCP-positive or anti-CCP-negative, and outcomes were evaluated in the 6 months post-index. Results: There were 217 anti-CCP-positive and 191 anti-CCP-negative RA patients included in the study. A higher proportion of anti-CCP-positive patients were initiated on RA treatment than anti-CCP-negative patients (70.5% vs 23.0%; p < .0001). More anti-CCP-positive patients received methotrexate (73.2% vs 56.8%; p = .0374), while more anti-CCP-negative patients received hydroxychloroquine (31.8% vs 13.1%; p = .0037) in first-line therapy. A higher proportion of anti-CCP-negative patients were tested for rheumatoid factor (RF) and erythrocyte sedimentation rate (ESR). Of those tested, there were more positive test results in the anti-CCP-positive cohort compared to the anti-CCP-negative cohort (RF: 84.4% vs 18.2%, p < .0001; C-reactive protein [CRP]: 69.7% vs 48.3%, p = .0008; and ESR: 89.5% vs 53.9%, p < .0001). Outpatient utilization predominated, with more anti-CCP-positive patients having any outpatient physician office visit (96.3% vs 77.5%, p < .0001) and a higher mean number of visits (5.3 vs 2.5, p < .0001) than anti-CCP-negative patients. Among anti-CCP-positive ( n = 113) and anti-CCP-negative ( n = 58) patients with imaging results, more anti-CCP-positive patients had joint erosion compared to anti-CCP-negative patients (18.6% vs 8.6%; p = .0858); however, statistical significance was not reached. Conclusion: RA patients with positive anti-CCP antibodies had higher degrees of inflammation and disease activity as indicated by laboratory results, which likely contributed to their higher rates of healthcare utilization, joint erosion, and proportions of RA treatment.